Construção de um plano operativo em uma comunidade agroextrativista na Amazônia: um relato de experiência - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Health is understood as a process that is influenced by several determinants whether these are ecological or social-cultural. Health management is directly linked to the surveys of the real needs of each territory, since knowing the needs of the community can make effective decisions and measures. And as a fundamental part of this process is the realization of a planning based on the individual and collective perception of different actors who are linked to the problems, who interact in the formulation of the action plan and who have governance over the problems. In this context, we sought to carry out a Strategic Situational Planning (PES) with reference to Carlos Matus economist. This work intends to report the experiences from the participation in the process of construction of the PES with a focus on normative moment, in the community of Irurama, Pará. This is an experience report of a critical-reflective approach of descriptive character about the academic experiences in the (IBR) of the Interdisciplinary Bachelor of Health (BIS) course, of the Universidade Federal do Oeste do Pará (Ufopa), being carried out in the rural community, Irurama, which is located at Everaldo Martins Highway (PA 457), in the Alter do Chão/Santarém stretch in the Eixo Forte Região. The articulation between the leaderships and the main related actors was an important point for the execution of the work, considering the necessity of participation the governmental or private organs, associations, religious institutions and community groups, as well as all the institutions directly involved with the problematic, which are fundamental to its realization. As a result, questions were raised regarding the aspects that were perceived as problems for the community, and with a process of understanding the problems, one can identify the vulnerability in which the community was involved. In general, participation in the process of construction of the operational plan allowed interaction with community families, community leaders, teachers, managers, health professionals, public agents, who are actors that have governance over the territory at different levels, with different and divergent interests in the "social game" and, in this way, create an intense environment that instigated us to the improvement of the knowledge and skills acquired in a continuous process of learning.
Keywords: Gestão em Saúde; Políticas Públicas; Planejamento Participativo; CNPQ:: CIÊNCIAS DA SAÚDE